Epidemiology and Antifungal Susceptibility Profile of Aspergillus Species: Comparison between Environmental and Clinical Isolates from Patients with Hematologic Malignancies - Cho, Sung-Yeon (J Clin Microbiol, 2019)
Global data on the epidemiology and susceptibility of Aspergillus are crucial in the management of invasive aspergillosis. Here, we aimed to determine the characteristics of clinical and environmental Aspergillus isolates, focusing mainly on hematologic malignancy patients. We prospectively collected all consecutive cases and clinical isolates of culture-positive proven/probable invasive aspergillosis patients from January 2016 to April 2018 and sampled the air inside and outside the hospital. Cryptic species-level identification of Aspergillus, antifungal susceptibilities, and cyp51 gene sequencing were performed, and clinical data were analyzed. This study was conducted as part of the Catholic Hematology Hospital Fungi Epidemiology (CAFÉ) study. A total of 207 proven/probable invasive aspergillosis and 102 clinical and 129 environmental Aspergillus isolates were included in this analysis. The incidence of proven/probable invasive aspergillosis was 1.3 cases/1,000 patient-days during the study period. Cryptic Aspergillus species accounted for 33.8%, with no differences in proportions between the clinical and environmental isolates. Section Nigri presented a high proportion (70.5%) of cryptic species, mainly from A. tubingensis and A. awamori: the former being dominant in environmental samples, and the latter being more common in clinical isolates (P < 0.001). Of 91 A. fumigatus isolates, azole-resistant A. fumigatus was found in 5.3% of all A. fumigatus isolates. Three isolates presented the TR(34)/L98H mutation of the cyp51A gene. Patients with invasive aspergillosis caused by azole-resistant A. fumigatus showed 100% all-cause mortality at 100 days. This study demonstrates the significant portion of cryptic Aspergillus species and clinical implications of azole resistance and underscores the comparison between clinical and environmental isolates.